THE SPATIAL AND TEMPORAL DIVERSIFICATION OF EARLY PALAEOZOIC VERTEBRATES - Smith M.P.; Donoghue P.C.J.; Sansom I.J. (My University, 2002)
Recent discoveries have dramatically altered traditional views of the stratigraphic distribution and phylogeny of Early Palaeozoic vertebrates and permit a reappraisal of biogeographic patterns and processes over the first 120 million years of vertebrate evolution. Stratigraphic calibration of the phylogenetic trees indicates that most of the pre-Silurian record can be inferred only through ghost ranges. Assessment of the available data suggests that this is due to a shift in ecological niches after the latest Ordovician extinction event and a broadening of geographical range following the amalgamation of Euramerica during the early Silurian. Two major patterns are apparent in the biogeographic data. Firstly, the majority of jawless fishes with dermoskeletal, plated ‘armour’ were highly endemic during Cambrian-Ordovician time, with arandaspids restricted to Gondwana, galeaspids to China, and anatolepids, astraspids and, possibly, heterostracans confined to Laurentia. These Laurentian groups began to disperse to other continental blocks as the ‘Old Red Sandstone continent’ amalgamated through a series of tectonic collisions. The second major pattern, in contrast, encompasses a number of microsquamous and naked, jawed and jawless primitive vertebrates such as conodonts, thelodonts, placoderms, chondrichthyans and acanthodians, which dispersed rapidly and crossed oceanic barriers to attain cosmopolitan distributions, although many have Laurentian origins. A clear difference in dispersal potential exists between these two types of fishes. Overall, the development of biogeographic patterns in Early Palaeozoic vertebrates involved a complex interaction of dispersal, vicariance and tectonic convergence.